The Regional Distribution of Surface Mass Balance in Mizuho Plateau, Antarctica - Yamada, Tomomi; Wakahama, Gorow (1981)
P(論文) Mizuho Plateau is classified into an ablation zone and three different accumulation zones from the regional distribution of thickness of the annual layer accumulated snow measured during ten years beginning in 1968 using the snow stake method, and from the locations of the ablation area provided by images of ERTS satellite. A snow stake along a traverse route gave the thickness of the annual layer at a given place in a given year; the thickness there in another year in which measurements were not made was obtained by extrapolation, using a value of annual variation in areal average in each of the zones; then, the thickness was averaged over the ten years. In addition, stratigraphic data provided thicknesses and the density profile of the surface layers at a given place. Consequently, contours indicating the surface mass balance averaged over the ten years were obtained and delineated on the topographical map of Mizuho Plateau. It was then derived from the contour map that the total mass inputs in the Shirase and the Soya drainage basin are respectively 15.5 and 1.2Gt/yr. Moreover, from the result of discussions of the general role concerning the characteristics of the distribution of the mass balance related to the topography, the emergence/submergence flow of the ice sheet and the action of katabatic winds, it is suggested that the positive and the negative balance take place on the surface of the ice sheet in such a direction that the unilateral changes due to the perturbation deposition of solid precipitation and the vertical flow of the ice sheet cancel out, resulting in the maintenance of the morphological features of the ice sheet. departmental bulletin paper